Hibridisasi masakan Melayu: Kajian kes di Kuala Lumpur / Abd. Razak Aziz - Abd. Razak , Aziz (2018)
In this modern globalized world, Malay culinary culture is in constant innovative mode. The influx of external cultural elements are affecting its traditional gastronomic microcosm. The practice of adapting foreign food culture among the Malay chefs, using modern techniques and presentation, not only prove problematic, but also has the potential to destroy the local gastronomic heritage. This research, therefore, explores the implication of globalization through various “scape” and how Malay chefs have to adapt to the global food trend. To understand how the Malay chefs respond to these phenomena, this research will analyse the activities taking place in their kitchen. This research adopts an in-depth interview and observation data collection methods. This approach enables the researcher to signify the transformation at the macro level in term of modernization and globalization into micro practices of everyday culinary activities. Chefs are passionate about their culinary aesthetics, and at the same time they have to be concerned about the business profitability. This will dictate how these chefs decide on their culinary priorities. This study discovers that one prevalent problem with Malay food is the unclear concept and lack of customer appeal, particularly in a full-service restaurant environment. In response to these circumstances, the chefs tried to find ways of a addressing these challenges. The research concludes that the idea of using “scape” is a suitable tool to build a reliable Malay culinaryscape that will determine the future of Malay cuisine in the wave of modernization.